Comparison between clinical grading and navigation data of knee laxity in ACL-deficient knees - Yamamoto Yuji; Ishibashi Yasuyuki; Tsuda Eiichi; Tsukada Harehiko; Maeda Shugo; Toh Satoshi (BMC, 2010)
Abstract Background The latest version of the navigation system for anterior cruciate ligament (ACL) reconstruction has the supplementary ability to assess knee stability before and after ACL reconstruction. In this study, we compared navigation data between clinical grades in ACL-deficient knees and also analyzed correlation between clinical grading and navigation data. Methods 150 ACL deficient knees that received primary ACL reconstruction using an image-free navigation system were included. For clinical evaluation, the Lachman, anterior drawer, and pivot shift tests were performed under general anesthesia and were graded by an examiner. For the assessment of knee stability using the navigation system, manual tests were performed again before ACL reconstruction. Navigation data were recorded as anteroposterior (AP) displacement of the tibia for the Lachman and anterior drawer tests, and both AP displacement and tibial rotation for the pivot shift test. Results Navigation data of each clinical grade were as follows; Lachman test grade 1+: 10.0 mm, grade 2+: 13.2 ± 3.1 mm, grade 3+: 14.5 ± 3.3 mm, anterior drawer test grade 1+: 6.8 ± 1.4 mm, grade 2+: 7.4 ± 1.8 mm, grade 3+: 9.1 ± 2.3 mm, pivot shift test grade 1+: 3.9 ± 1.8 mm/21.5° ± 7.8°, grade 2+: 4.8 ± 2.1 mm/21.8° ± 7.1°, and grade 3+: 6.0 ± 3.2 mm/21.1° ± 7.1°. There were positive correlations between clinical grading and AP displacement in the Lachman, and anterior drawer tests. Although positive correlations between clinical grading and AP displacement in pivot shift test were found, there were no correlations between clinical grading and tibial rotation in pivot shift test. Conclusions In response to AP force, the navigation system can provide the surgeon with correct objective data for knee laxity in ACL deficient knees. During the pivot shift test, physicians may grade according to the displacement of the tibia, rather than rotation.